Research and Application of a Clear Diamond-Shaped Distribution Network Structure - Shengli, Liu; Jun, Wu; Longjiang, Xue; Di, Wu; Haiqing, Lu; Wenlong, Li; Shaofang, Wang; Wenqi, Li (Frontiers in Energy Research, 2021)
Aiming at the problems of low power supply reliability, poor transfer capacity between stations, and low line utilization in the current distribution network, this paper proposes a diamond-shaped distribution network structure with a clear structure. First, we investigated the typical wiring patterns of medium-voltage distribution networks in Tokyo, Japan, Paris, France and domestic developed cities, and summarized experience and shortcomings. Secondly, combining the typical wiring patterns of domestic and foreign distribution networks, construct a diamond-shaped distribution network structure, and study its adaptability, safety and flexibility, power supply reliability, and economy. Finally, take the transformation of the wiring mode of a regional distribution network in a certain city as an example, compare the use of the diamond-shaped distribution network structure in this article with the use of cable double-ring network wiring, cable "double petal" wiring, and Shanghai diamond-type wiring distribution network grid reconstruction The effect verifies the superiority of the diamond-shaped distribution network structure in this paper.